Stroke Outcomes in the COMPASS Trial. Issue 9 (26th February 2019) - Sharma, Mukul; Hart, Robert G.; Connolly, Stuart J.; Bosch, Jackie; Shestakovska, Olga; Ng, Kelvin K.H.; Catanese, Luciana; Keltai, Katalin; Aboyans, Victor; Alings, Marco; Ha, Jong-Won; Varigos, John; et al.
Abstract : Background: Strokes were significantly reduced by the combination of rivaroxaban plus aspirin in comparison with aspirin in the COMPASS trial (Cardiovascular Outcomes for People Using Anticoagulation Strategies). We present detailed analyses of stroke by type, predictors, and antithrombotic effects in key subgroups. Methods: Participants had stable coronary artery or peripheral artery disease and were randomly assigned to receive aspirin 100 mg once daily (n=9126), rivaroxaban 5 mg twice daily (n=9117), or rivaroxaban 2.5 mg twice daily plus aspirin (n=9152). Patients who required anticoagulation or had a stroke within 1 month, previous lacunar stroke, or intracerebral hemorrhage were excluded. Results: During a mean follow-up of 23 months, fewer patients had strokes in the rivaroxaban plus aspirin group than in the aspirin group (83 [0.9% per year] versus 142 [1.6% per year]; hazard ratio [HR], 0.58; 95% CI, 0.44–0.76; P <0.0001). Ischemic/uncertain strokes were reduced by nearly half (68 [0.7% per year] versus 132 [1.4% per year]; HR, 0.51; 95% CI, 0.38–0.68; P <0.0001) by the combination in comparison with aspirin. No significant difference was noted in the occurrence of stroke in the rivaroxaban alone group in comparison with aspirin: annualized rate of 0.7% (HR, 0.82; 95% CI, 0.65–1.05). The occurrence of fatal and disabling stroke (modified Rankin Scale, 3–6) was decreased by the combination (32 [0.3% per year] versus 55 [0.6% per year]; HR, 0.58; 95% CI, 0.37–0.89; P =0.01). Independent predictors of stroke were prior stroke, hypertension, systolic blood pressure at baseline, age, diabetes mellitus, and Asian ethnicity. Prior stroke was the strongest predictor of incident stroke (HR, 3.63; 95% CI, 2.65–4.97; P <0.0001) and was associated with a 3.4% per year rate of stroke recurrence on aspirin. The effect of the combination in comparison with aspirin was consistent across subgroups with high stroke risk, including those with prior stroke. Conclusions: Low-dose rivaroxaban plus aspirin is an important new antithrombotic option for primary and secondary stroke prevention in patients with clinical atherosclerosis. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01776424. Abstract : Supplemental Digital Content is available in the text.